Rancang Bangun Pengendali Pintu Gerbang Tol Dengan RFID Menggunakan Logika Fuzzy - Muhammad Raihan Al Hakim; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Congestion that occurs at the toll gate is due to the increased volume of vehicles that cannot be accommodated by the road capacity and the payment system that is running is unable to overcome the congestion. Based on this, a system developed that helps efforts to minimize congestion at toll gates using the Fuzzy method. As an observer of the density condition, Ultrasonic sensor is used, as a payment instrument as well as the vehicle size reader used RFID RC522, the system output is used by the servo as the toll gate and then processed in the Arduino Mega 2560 microcontroller. the min implication process and Fuzzy system inference are max, from the inference stage followed by the defuzzification process and obtained a strict value for servo in determining the duration of the opening of the toll gate. In testing, the Ultrasonic sensor has the same measurement in measuring distance using a ruler. RFID as a system interface produces fast reading accuracy and has a maximum reading distance of 1 cm. The system output has a difference in the difference in servo position degree measurement with manual measurement of 2.4 degrees and an error of 3.766%. After the system is implemented, the results of the system calculation are then compared with the sample data obtained from several experiments, overall the calculation of Fuzzy logic on the opening time of the toll gate has an error percentage of 4.189%.